Review and determining the influence of zeolite on concrete strength under high temperature conditions - Sharif Jadidi, Mahdi; Mohammad Ranjbar, Malek (International Journal of Engineering and Technology, 2016)
in this paper, to verify the effect of zeolite on the strength of concrete and the effect of high temperatures on this type of concrete 5 composition, containing different percentages zeolite (5%, 10%, 15% and 20%) with fixed water to cement ratio for perception of optimized percent of zeolite is made and influence of heat on compressive strengthÂ and ultrasonicÂ speed wavesÂ was checked . according to tests, it is concluded that the replacement of 10% cement with zeolite at ratio water to cement 0.45 at ages 7, 28 and 90 days, is the optimized replacement level to zeolite.